Improving the Creativity and Innovation of Counseling Teachers through Digital Guidance Media “Wahana Bikons”: Peningkatan Kreativitas dan Inovasi Guru BK Melalui Media Bimbingan Digital “Wahana Bikons” - Citra Tectona Suryawati; Ma’rifatin Indah Kholili; Agus Tri Susilo; Rian Rokhmad Hidayat; Ribut Purwaningrum; Asrowi; Adi Dewantoro; Ulya Makhmudah; Naharus Surur; Syifaa' Nur Hanifah; Agustina Miftakhul Jannah (Universitas Lancang Kuning, 2025)
The purpose of community service activities is to train BK teachers in utilizing the Wahana Bikons platform to improve creativity and innovation in creating game-based service media in guidance and counseling services. The implementation of community service involved 40 vocational high school guidance and counseling teachers in Karanganyar Regency. The training activity method is In and On for 2 days equivalent to 16 hours of training, with the division on the first day being the delivery of material and simulation, while the second day is implementation in schools. The data collection technique uses pre-test and post-test instruments which are analyzed using a different test (paired sample t-test). The results of the Paired Samples Statistics test show that the average pre-test score is 24.62 and the post-test is 29.17. This shows that the average participant score increased by 4.55 points after training. These results show that the creativity of BK teachers in using digital media in guidance and counseling services is increasing.